Cross-Industry Innovation Processes: Strategic Implications for Telecommunication Companies - Hahn, Tobias (Springer, 2015)
Based on multiple case study analysis, focusing on scalable service innovation, the present study provides a practical process model that shall serve telecommunication companies as a guideline while conducting strategic cross-industry innovation projects. The findings also pay attention to characteristics in cross-industry collaboration, organizational preconditions and strategic deliberations and postulate propositions for present theoretical innovation process models.